1995
DOI: 10.1111/j.1745-6584.1995.tb00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Leaching Near the Waiawa Shaft, Oahu, Hawaii: 2. Modeling Results

Abstract: This paper is the second part of a two‐part series concerned with assessing the potential for organic chemical leaching to a ground‐water skimming tunnel in the Pearl Harbor Basin, Oahu, Hawaii, as a direct result of proposed urban development. The Pesticide Root Zone Model (PRZM) was used, after testing with field and laboratory data described in the companion paper, to make long‐term predictions of the movement of chlorpyrifos, diazinon, metribuzin, and nitrate under various recharge scenarios. The PRZM simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Preferential flow and transport in oxisols was not considered in this study, although these soils are known to exhibit preferential flow and transport 45, 46. The reasons for neglecting possible preferential flow and transport in weathered oxisols were twofold: (i) the type of field observations (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Preferential flow and transport in oxisols was not considered in this study, although these soils are known to exhibit preferential flow and transport 45, 46. The reasons for neglecting possible preferential flow and transport in weathered oxisols were twofold: (i) the type of field observations (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that the use of a single set of input parameters for different agricultural seasons might not lead to a good description of results over the entire experimental period,15, 26, 35, 36 especially under circumstances where droughts are experienced 13. Other examples of limited extrapolation are the use of an application rate different from that used in the calibration11, 33 and the simulation of leaching deeper than the profile depth used during calibration 37…”
Section: The Use Of Calibration In Modelling the Environmental Fatementioning
confidence: 99%
“…These include simple index models1–6 and transient and deterministic simulation models 7–10. Models of the latter type have been used in several research studies11–15 as well as in regulatory contexts16, 17 to evaluate pesticide leaching to groundwater. Index models have been used to assess the leaching potential of pesticides18–20 and as part of decision support systems,21 and they are often considered suitable for relative vulnerability assessments.…”
Section: Introductionmentioning
confidence: 99%